The Role of Life Review on Life expectancy and Family Cohesion Among Mental Retardation Students - Hossein Jenaabadi; Jafar Ramezani (Iranian Evolutionary Educational Psychology Journal, 2020)
The purpose of this study was to determine the role of life review on life expectancy and family cohesion among mental retardation students. The present study was a quasi-experimental study of two groups with pre-test and post-test and the statistical population was comprised of all students with mental retardation in the secondary school of Birjand that according to the physician, did not have mental retardation and psychological disorders also they had ability to answer questions and willingness to cooperate. The statistical sample of research consisted of 40 subjects who were voluntarily selected and randomly divided equally into two experimental and control groups. Measurement tool was Miller life expectancy questionnaire (1988) and Olson family cohesion (1991). First, all the samples responded to the questionnaires. Then, a treatment plan of life review was performed for the experimental group based on Haight and Webster's life review (1995) at 8 sessions (each session 60 minutes), and the post-test was taken from the experimental and control group. Data were analyzed using covariance analysis and SPSS16 software. The results showed that life review has been effective in increasing the life expectancy and family cohesion of mental retardation students.